Assessing key soft skills in organizational contexts: development and validation of the multiple soft skills assessment tool - Colledani, Daiana; Robusto, Egidio; Anselmi, Pasquale (Frontiers in Psychology, 2024)
Soft skills, also known as transversal skills, have gained significant attention in the organizational context due to their positive impact on various work-related outcomes. The present study aimed to develop and validate the Multiple Soft Skills Assessment Tool (MSSAT), a short self-report instrument that evaluates interpersonal skills (initiative-resourcefulness, assertiveness, conflict management), interpersonal communication skills, decision-making style (adaptive and maladaptive), and moral integrity. The scale development process involved selecting and adapting relevant items from existing scales and employing a cross-validation approach with a large sample of workers from diverse organizational settings and job positions (N = 639). In the first step, 28 items were carefully chosen from an item pool of 64 items based on their content, factor loadings, item response theory analyses, differential item functioning, and fit statistics. Next, the structure of the resulting scale was evaluated through confirmatory factor analyses. The MSSAT demonstrated gender invariance and good reliability and validity. The results of a network analysis confirmed the relationships between soft skills and positive work-related outcomes. Notably, interpersonal communication skills and moral integrity emerged as crucial skills. The MSSAT is a valuable tool for organizations to assess the soft skills of their employees, thereby contributing to design targeted development programs.